Melioidotic prostatic abscess in Pahang - Ng, Teck Han; How, Soon Hin; Abdul Rashid, Mohd Amran; Md Ralib @ Md Raghib, Ahmad Razali; Kuan, Yeh Chunn (Singapore Medical Association, 2009)
Melioidosis is caused by Burkholderia pseudomallei, a Gram-negative bacillus. Melioidosis can affect many organs, including the prostate. However, prostatic abscess due to melioidosis is uncommon. We describe five cases of melioidosis with prostatic abscess. Four of five patients had diabetes mellitus and had more than one organ involvement. The diagnosis of prostatic abscess in our patients was only made with computed tomography of the abdomen and pelvis. None of our patients underwent surgical drainage and all remained well after treatment with antibiotics, except for one mortality secondary to severe septicaemia.